Analisis Keuntungan Investasi Emas Dengan Ihsg - Ihsan Kurniawan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Before investing, investors should do return of investment analysis. This study is to determine the differences of return between gold investment and IHSG stock. This study period is between November 2009 to October 2018 with timespan of 1 year, 5 years, and 10 years. The data used for this study is IHSG stock prices historical data, and the price of LBMA gold. Data analysis using T-test (independent sample t-test). The results of this study shows that investing in gold instrument return higher profit than investing in IHSG stocks.